The applicability of physical optics in the millimetre and sub-millimetre spectral region. Part II: Application to a three-component model of ice cloud and its evaluation against the bulk single-scattering properties of various other aggregate models. (February 2018) - Baran, Anthony J.; Ishimoto, Hiroshi; Sourdeval, Odran; Hesse, Evelyn; Harlow, Chawn
Highlights: Various ice aggregate single-scattering properties are compared in the microwave. Hollow rosettes and Voronoi models scatter similarly to each other in the microwave. Microwave linear polarisation may discriminate between compact and spatial ice aggregates. Microwave single-scattering databases should consider up to five cm-sized particles. Current PSD parameterisations are insufficiently broad to apply in the microwave. Abstract: The bulk single-scattering properties of various randomly oriented aggregate ice crystal models are compared and contrasted at a number of frequencies between 89 and 874 GHz. The model ice particles consist of the ten-branched plate aggregate, five-branched plate aggregate, eight-branched hexagonal aggregate, Voronoi ice aggregate, six-branched hollow bullet rosette, hexagonal column of aspect ratio unity, and the ten-branched hexagonal aggregate. The bulk single-scattering properties of the latter two ice particle models have been calculated using the light scattering methods described in Part I, which represent the two most extreme members of an ensemble model of cirrus ice crystals. In Part I, it was shown that the method of physical optics could be combined with the T-matrix at a size parameter of about 18 to compute the bulk integral ice optical properties and the phase function in the microwave to sufficient accuracy to be of practical value. Here, the bulk single-scattering properties predicted by the two ensemble model members and the Voronoi model are shown to generally bound those of all other models at frequencies between 89 and 874 GHz, thus representing a three-component model of ice cloud that can be generally applied to the microwave, rather than using many differing ice particle models. Moreover, the Voronoi model and hollow bullet rosette scatter similarly to each other in the microwave. Furthermore, from the various comparisons, the importance of assumed shapes of the particle size distribution as well as cm-sized ice aggregates is demonstrated.